2010
DOI: 10.4314/ajpsy.v13i1.53430
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among secondary school students in an urban setting in Nigeria: prevalence and associated factors

Abstract: Objective: Substance use continues to be major risk behaviour among youth, with consequent physical and /or mental health complications. The current study aimed to establish the prevalence and associated factors of substance use among selected secondary school students in Lagos. Method: This was a cross-sectional and descriptive study among selected secondary school students in Lagos. Permission was obtained from appropriate school authorities; as well as consent from each participant. The WHO Students' Drug U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
148
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(193 citation statements)
references
References 16 publications
33
148
12
Order By: Relevance
“…A significant number of students consume Khat to be alert and wakeful at night, especially during examination periods (EPHA). Availability of substances, age, gender, having friends and families who use substances were the commonly mentioned factors that influence substances use [3][4][5]. Of the young segment of the Ethiopian population, college and University students are the most at risk of using alcohol and other drugs such as Khat and tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of students consume Khat to be alert and wakeful at night, especially during examination periods (EPHA). Availability of substances, age, gender, having friends and families who use substances were the commonly mentioned factors that influence substances use [3][4][5]. Of the young segment of the Ethiopian population, college and University students are the most at risk of using alcohol and other drugs such as Khat and tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is widely masticated among youth Ethiopians, especially high school, college and university students (Damena et al, 2011). Its effects on the chewers include increased levels of energy, increased self-esteem, euphoria, increased libido, excitement, and increased proclivity for social interaction (Deressa & Azazh, 2011;Oshodi et al, 2010). Even though khat chewing has addictive and negative physical, economical and social connotation effects, it has positive economic, social and medicinal values (Lemessa, 2001).…”
mentioning
confidence: 99%
“…The above mentioned investigators findings depicted that there were many factors associated with khat chewing among students. Of which, most studies (Deressa & Azazh, 2011;Oshodi et al, 2010;EPHA, 2006) showed that being male, having peers who chewed khat, having family members who chewed khat, residence place, religion and seniority in the case of college/university students were statistically significant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance to Abianwu (2005) (33) , who stressed that cannabis is by far the most commonly used illicit drug with the usage of 4% of the world population compared to 1% for all other drugs combined. Oshodi et al, (2010) (34) , also explained in their study that marijuana is the most commonly used substance followed by tobacco. They further confirmed that in the United Kingdom, crosssectional studies have shown that among students aged 15-16 years, at least 40% had used illicit drugs, mainly cannabis, at some time during their lives.…”
Section: Discussionmentioning
confidence: 91%